From the epididymis to the egg: participation of CRISP proteins in mammalian fertilization - Da Ros, Vanina Gabriela (2015)
Mammalian fertilization is a complex process that involves different steps of interaction between the male and female gametes. In spite of its relevance, the molecular mechanisms underlying this process still remain to be elucidated. The present review describes the contribution of our laboratory to the understanding of mammalian fertilization by using CRISP (Cysteine-RIch Secretory Proteins) as model molecules. Substantial evidence obtained using in vitro assays and knockout models shows that epididymal CRISP1 associates with the sperm surface with two different affinities during maturation and participates in the regulation of signaling pathways during capacitation as well as in both sperm-zona pellucida interaction and gamete fusion. These observations can be extended to humans as judged by our findings showing that the human homologue of the rodent protein (hCRISP1) is also involved in both stages of fertilization. Evidence supports that other members of the CRISP family secreted in the testes (CRISP2), epididymis (CRISP3-4) or during ejaculation (CRISP3) are also involved in sperm-egg interaction, supporting the existence of a functional redundancy and cooperation between homologue proteins to ensure the success of fertilization. Together, our observations indicate that CRISP proteins escort sperm along their transit through both the male and female reproductive tracts. We believe these results not only contribute to a better mechanistic understanding of fertilization but also support CRISP proteins as excellent candidates for future research on infertility and contraception.